Meningkatkan Kemampuan Representasional pada Konsep Larutan Penyangga dengan Prototype E-Book Berbasis Intertekstual - Nur Sehasari Dewi (Prosiding Temu Ilmiah Nasional Guru, 2022)
: The inability of students to visualize structures and processes at the submicroscopic ormolecular level can lead to misconceptions. The aim of the research is to improve therepresentational ability of the concept of buffer solution with an intertextual-based E-Bookprototype. The research method is through a literature study of 40 national and internationalarticles that focus on intertextual, three levels of representation, e-books, buffer solutions andrepresentational and literature studies of chemical buffer solutions textbooks. From the results ofthe Intertextual literature study, it can be a learning strategy for students to build understandingthrough various levels of chemical representations that are relevant to students' everydayexperiences. Learning resources that can present verbal, audio, animated and 3D images areinteractive e-books. The results of the research are one of the efforts to improve Representationalskills in buffer solutions, namely e-books that are intertextual based because they can provideopportunities for students to visualize concepts in chemistry that are abstract in nature and requirevisualization.